ХАРАКТЕРИСТИКА ДЕВІАНТНОЇ ПОВЕДІНКИ ПІДЛІТКІВ І ПРИЧИНИ ЇЇ ВИНИКНЕННЯ (Педагогіка вищої та середньої школи, 2022)
The artikale includes the analysis of special literature concerning characteristics of deviation behaviour teenager andcause its beginning.